2010
DOI: 10.1051/0004-6361/200913700
|View full text |Cite
|
Sign up to set email alerts
|

Absolute dimensions of eclipsing binaries

Abstract: Context. Double-lined, detached eclipsing binaries are our main source for accurate stellar masses and radii. This paper is the first in a series with focus on the upper half of the main-sequence band and tests of 1-2 M evolutionary models. Aims. We aim to determine absolute dimensions and abundances for the detached eclipsing binary V1130 Tau, and to perform a detailed comparison with results from recent stellar evolutionary models. Methods. uvby light curves and uvbyβ standard photometry have been obtained w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…When compared with the log Z/Z U V = −0.28 tracks (most similar to the best-fit metallicity of −0.31), however, both components fall along the corresponding mass track within the uncertainties. While this slightly higher metallicity appears to bring our observations in line with the models, we note that Clausen et al (2010) similarly found the components of V1130 Tau (1.31M and 1.39M , 1.49R and 1.78R , 6650 K and 6625 K, P = 0.8 d) approximately 200 K cooler then the corresponding Y 2 models (see their Figure 6) at their observed metallicity of log Z = −0.24 which may indicate a discrepancy with theory, although (like us) their abundances have not been derived in detail.…”
Section: Comparison With Evolutionary Modelssupporting
confidence: 74%
“…When compared with the log Z/Z U V = −0.28 tracks (most similar to the best-fit metallicity of −0.31), however, both components fall along the corresponding mass track within the uncertainties. While this slightly higher metallicity appears to bring our observations in line with the models, we note that Clausen et al (2010) similarly found the components of V1130 Tau (1.31M and 1.39M , 1.49R and 1.78R , 6650 K and 6625 K, P = 0.8 d) approximately 200 K cooler then the corresponding Y 2 models (see their Figure 6) at their observed metallicity of log Z = −0.24 which may indicate a discrepancy with theory, although (like us) their abundances have not been derived in detail.…”
Section: Comparison With Evolutionary Modelssupporting
confidence: 74%
“…Finally, we note that the ‘helium problem’ may not be limited to K dwarfs: systematic temperature offsets from the theoretical MS at low Z have been highlighted for FG dwarfs in the Geneva–Copenhagen survey (Nordström et al 2004); and a helium content Y = 0.23–0.24 (i.e. slightly subcosmological) has been recently suggested for a slightly metal‐poor F dwarf binary ([Fe/H]=−0.25; Clausen et al 2010). If the problem indeed extends to FG dwarfs, clearly some of the suggested solutions (for instance, those related to diffusion) are not viable.…”
Section: Summary and Discussionmentioning
confidence: 82%
“…VZ Hya, CTB08; V1130 Tau, Clausen et al 2010). It is, however, still too early to drawn any firm conclusions.…”
Section: Discussionmentioning
confidence: 99%